The influence of emotional intelligence on job performance of frontline service employees: the moderating role of service types / Abdul Kadir Othman and Syarifah Farrah Hanim Syed Muhsin. - Othman, Abdul Kadir; Syed Muhsin, Syarifah Farrah Hanim (Universiti Teknologi Mara Selangor, 2020)
Service organizations rely heavily on humans to deliver the service. The only difference is the level of dependency on the human aspect for different types of service. Professional service depends mostly on humans to deliver the service but mass service is the least dependent on human element when delivering the service. Therefore, investigating the role of emotional intelligence in influencing employee performance by looking at different types of service is crucial because it has been widely accepted that emotional intelligence is the panacea to poor employee performance. This study involved employees from three different types of service organizations; higher learning institutions, insurance agencies and banks. A series of moderated multiple regression analyses were performed to analyze the research data and the results indicate the significant relationship between use of emotion and job, the relationship between use of emotion and career role, and the relationship between use of emotion and team role. Regarding the moderating role of service types, the study found that professional service moderates the relationship between self-emotion appraisal and job role, the relationship between others emotion appraisal and job role, the relationship between regulation of emotion and organization role, the relationship between use of emotion and career role, and the relationship between use of emotion and innovator role. Service shop, on the other hand, moderates the relationship between self-emotion appraisal and job role, and the relationship between use of emotion and team role. The implications of the study are discussed in the paper.